(untitled) (Docentes 2.0 Journal, 2025)
Understanding Newton’s laws is fundamental to the study of physics and disciplines such as engineering, as they constitute the foundation for addressing more complex subjects. In this context, academic performance in subsequent subjects depends on mastery of these concepts. This research aimed to analyze the impact of using digital resources accompanied by teaching guides on the teaching-learning process of Newton’s laws, with the goal of improving students’ academic performance. The study was conducted under the sociocritical paradigm, using the action research method and a mixed-method approach. The sample consisted of 35 first-year high school students from the "Luis Cordero" Educational Unit, selected through purposive sampling. The instruments used were a pretest, a posttest, a validated survey (with Cronbach’s alpha), semi-structured interviews, and a documentary analysis of the teaching guide. Quantitative data were analyzed statistically to compare learning outcomes before and after the intervention, while qualitative data were processed using open and axial coding and organized into thematic categories. The integration of approaches was achieved through methodological triangulation, which strengthened the study’s validity. The results showed a significant improvement in grades following the intervention, along with an increase in student motivation and participation. It is concluded that digital resources, supported by teaching guides, constitute an effective, replicable, and relevant pedagogical strategy in educational contexts with limited resources.